2001
DOI: 10.1007/s006040170040
|View full text |Cite
|
Sign up to set email alerts
|

SEM-EDXRF Study of Two Chemical Modifiers Based on Platinum and Tungsten and Their Effect on ET-AAS Atomization of Lead

Abstract: The behavior of two chemical modi®ers based on platinum and tungsten, is studied in the two parts of this work. At ®rst, the chemical and morphological alterations of these during pyrolysis and atomization stages in electrothermal atomic absorption spectrometry are studied. The compounds were H 2 PtCl 6 and Na 2 WO 4 . A cylindrical graphite tube was used, and ®xed shaped rectangular graphite plates were put inside as platforms to prepare the specimens. The crystalline formations on the platforms were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Studies on the modifying effect of Pt and W on the atomization of Pb were reported in a two part article by Zachariadis et al 237 The crystalline formations left on graphite platforms after the pyrolysis and atomization of Pt and W compounds were studied using SEM and the chemical composition of the residues and the substrate investigated using EDXRF. The crystalline form of each modifier was found to change at temperatures between 500 and 1250 uC.…”
Section: Furnacesmentioning
confidence: 99%
“…Studies on the modifying effect of Pt and W on the atomization of Pb were reported in a two part article by Zachariadis et al 237 The crystalline formations left on graphite platforms after the pyrolysis and atomization of Pt and W compounds were studied using SEM and the chemical composition of the residues and the substrate investigated using EDXRF. The crystalline form of each modifier was found to change at temperatures between 500 and 1250 uC.…”
Section: Furnacesmentioning
confidence: 99%
“…Zacharadias [22] using scanning electron microscopy and energy dispersive X-ray spectra (SEM-ED XRF) studied the morphology of specimens arising after the temperature modification of the graphite tube by Na 2 WO 4 and H 2 PtCl 6 . This paper encouraged the author to undertake more detailed study to find the optimal conditions for graphite tube modification by (NH 4 ) 2 WO 4 .…”
Section: Introductionmentioning
confidence: 99%